A wide swing, high drive current output stage. Issue 1 (2nd January 2021) - Faraji Baghtash, Hassan
ABSTRACT: In this paper, a novel current output stage (COS) is introduced. Deliberately compose of class AB operation and a special voltage sense and current compensation scheme enables the structure to operate at extreme voltage beyond the triode limits to achieve wide voltage dynamic range and grants it such following ever demanded merits at power supplies of 1.8V: low power consumption of 40 µW, high drive to bias current ratio of 100. The results are verified by Spectre post-layout simulation using 0.18 µm CMOS standard technology of TSMC. The process, the stability and robustness of the proposed COS are verified by stepwise response and Monte Carlo and corner simulations, respectively.